Climate Change and Economic Activity: Evidence from U.S. States - Kamiar Mohaddes; Ryan N. C. Ng; M. Hashem Pesaran; Mehdi Raissi; Jui-Chung Yang (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the long-term macroeconomic effects of climate change across 48 U.S. states over the period 1963.2016 using a novel econometric strategy which links deviations of temperature and precipitation (weather) from their long-term moving-average historical norms (climate) to various state-specific economic performance indicators at the aggregate and sectoral levels. We show that climate change has a long-lasting adverse impact on real output in various states and economic sectors, and on labour productivity and employment in the United States. Moreover, in contrast to most cross-country results, our within U.S. estimates tend to be asymmetrical with respect to deviations of climate variables (including precipitation) from their historical norms.
Keywords: C33; O40; O44; O51; Q51; Q54; 330; climate change; economic growth; adaptation; United States